Structural transition behavior in Indium chalcogenide thin films. (2019) - Pandian, M.; Matheswaran, P.; Gokul, B.; Sathyamoorthy, R.; Asokan, K.
Abstract: Phase change materials based Se-Te chalcogenides are key promoting technologies for electrical non volatile memory, named phase change memory (PCM). Indium chalcogenide In2 (Te1-x Sex )3 thin films was prepared by thermal evaporation technique in Ar atmosphere and followed by post anneal at 200 °C and 250 °C in Ar atmosphere. XRD spectra shows that thermal annealing lead to the structural transition of In2 (Te1-x Sex )3 into binary In2 Se3 and In2 Te3 phase. Significant change in crystallite size is observed with increase in the elemental composition of selenium concentration. The surface morphology of the as grown film shows spherical nature of the constituents. When the film annealed at 250 °C drives the compound formation of several phases via solid state reaction and the image contrast can be due to the phase transition of the In2 (Te1-x Sex )3 thin films. Band gap energy was estimated from optical spectra, which depends on the In2 Te3 and In2 (Te. Se)3 phase formation. The gradual decrease in the energy band gap with annealing is explained on the basis of structural transformation. The resistivity found to increases with increase in temperature for all the prepared In2 (Te1-x Sex )3 thin films